Diagnostic value of the posterior talofibular ligament area for chronic lateral ankle instability. Issue 5 (3rd February 2023) - Joo, Young; Moon, JeeYoun; Huh, Billy; Lee, Geung Kyu; Cho, Hyung Rae; Kang, Keum Nae; Lee, Sooho; Kim, Young Uk
Abstract : An injured posterior talofibular ligament (PTFL) is one of the reasons for chronic lateral ankle instability (CLAI). Previous researches have demonstrated that the PTFL thickness (PTFLT) is associated with chronic ligament injuries. However, ligament hypertrophy is different from ligament thickness. Thus, we created the PTFL cross-sectional area (PTFLCSA) as a diagnostic image parameter to assess the hypertrophy of the whole PTFL. We assumed that the PTFLCSA is a key morphological diagnostic parameter in CLAI. PTFL data were obtained from 15 subjects with CLAI and from 16 normal individuals. The T1-weighted axial ankle-MR (A-MR) images were acquired at the level of PTFL. We measured the PTFLT and PTFLCSA at the posterior aspect of the ankle using our imaging analysis program. The PTFLT was measured as the thickness between point of anterior and posterior fiber of PTFL. The PTFLCSA was calculated as the whole cross-sectional PTFL area. The average PTFLT was 3.43 ± 0.52 mm in the healthy group and 4.89 ± 0.80 mm in the CLAI group. The mean PTFLCSA was 41.06 ± 12.18 mm 2 in the healthy group and 80.41 ± 19.14 mm 2 in the CLAI group. CLAI patients had significantly greater PTFLT ( P < .001) and PTFLCSA ( P < .001) than the healthy group. A receiver operating characteristic curve analysis demonstrated that the optimal cutoff score of the PTFLT was 4.19 mm, with 93.3% sensitivity, 93.7% specificity, and an area under the curve of 0.97. The most suitable cutoff value of the PTFLCSA was 61.15 mm 2, with 93.3% sensitivity, 100% specificity, and area under the curve of 0.99. Even though the PTFLT and PTFLCSA were both significantly associated with CLAI, the PTFLCSA was a more exact morphological measurement parameter.